2017
DOI: 10.1002/oby.21867
|View full text |Cite
|
Sign up to set email alerts
|

Student obesity prevalence and behavioral outcomes for the Massachusetts Childhood Obesity Research Demonstration project

Abstract: ObjectiveExamine changes in prevalence of obesity and target health behaviors (fruit, vegetable, and beverage consumption; physical activity; screen time; sleep duration) among students from communities that participated in the Massachusetts Childhood Obesity Research Demonstration Project (MA-CORD) compared to controls.MethodsMA-CORD was implemented in two low-income communities. School-level prevalence of obesity among students in grades 1, 4 and 7 was calculated for the intervention communities and nine mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Figure describes the search results – 33 interventions were entered into the data corpus as meeting all inclusion criteria. Each intervention took place across multiple community settings and focused on systems change to promote healthy behaviours at the individual level applying a range of study designs . The interventions were participatory in nature, with a foundational component built on community engagement, empowerment and capacity building.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure describes the search results – 33 interventions were entered into the data corpus as meeting all inclusion criteria. Each intervention took place across multiple community settings and focused on systems change to promote healthy behaviours at the individual level applying a range of study designs . The interventions were participatory in nature, with a foundational component built on community engagement, empowerment and capacity building.…”
Section: Resultsmentioning
confidence: 99%
“…Schools were the primary setting for data collection in 29 of 33 interventions (10)(11)(12)(13)15,19,(45)(46)(47)(48)(49)(50)(51)(52)(53)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)66), and barriers around recruiting, engaging and following up with schools were frequently reported (11,50,57). Logistically, working around school timetables and vacation periods proved challenging (11), and one intervention noted that several visits to schools were often necessary to re-measure all participants in the follow-up period (50).…”
Section: Resultsmentioning
confidence: 99%
“…By working with MDPH, WIC, and several other existing infrastructures, we strengthened the ability to scale up the MA‐CORD model to disseminate evidence‐based interventions. Finally, although this paper reports outcomes in WIC‐enrolled children, child BMI and target behaviors were measured in primary care and school settings, and findings are reported elsewhere in this issue of Obesity . Thus, MA‐CORD truly represents a multisector approach to implementation and evaluation of childhood obesity prevention interventions in low‐income communities.…”
Section: Discussionmentioning
confidence: 99%
“…As a viable alternative, we used a longitudinal, quasi‐experimental design with a TAU group and collected outcome data from groups before and after the study implementation. Second, the MA‐CORD clinical intervention activities were embedded within other MA‐CORD interventions in WIC, public schools, and after‐school programs . Our process measures indicated that a large majority of eligible families were enrolled in WIC and school‐age children were enrolled in the local public schools.…”
Section: Discussionmentioning
confidence: 99%